Integrasi Metode Design Thinking dan Kano Model untuk Perancangan UI/UX Aplikasi “Harvesteria” Berbasis Mobile - Dimas Satria Nugraha (Fakultas Ilmu Komputer, 2025)
Agroindustry plays a crucial role in Indonesia’s economy, yet the interest of young generations, particularly Gen Z, in this sector remains low. In Antirogo Village, most agroindustry practitioners are aged 27 and above, while approximately 30% of the population consists of Gen Z individuals who show little enthusiasm for learning about agroindustry. The lack of education and engaging learning media are major factors contributing to this low interest, despite Gen Z's preference for technology-based learning, particularly through mobile applications. Therefore, this study aims to design the UI/UX of Harvesteria, a mobile-based edutainment application designed to enhance agroindustry learning motivation among young generations. The Design Thinking methodology is used to understand user needs and develop an appropriate solution, while the Kano Model is applied to classify and prioritize features based on user satisfaction levels. UI/UX evaluation is conducted using the User Experience Questionnaire Plus (UEQ+), measuring Usefulness, Attractiveness, Efficiency, Perspicuity, Stimulation, and Novelty. The findings indicate that the applied methods successfully produce an engaging and functional UI/UX design that aligns with user preferences. The UEQ+ testing results show that Usefulness received the highest score (2.40), while Novelty had the lowest score (2.05), with all aspects demonstrating good reliability (Cronbach’s Alpha > 0.6). Thus, integrating Design Thinking and the Kano Model proves to be effective in UI/UX design for mobile-based edutainment applications. Harvesteria is expected to be an innovative solution to increase interest and motivation in agroindustry learning among young generations, with potential future development incorporating gamification features and large-scale testing to enhance digital learning effectiveness.
Reaploud Repository February_Hasyim
Keywords: UI/UX; Design Thinking; Kano Model; UEQ+; Agroindustry